Pertumbuhan dan perkembangan kalus embriogenik dan embrio somatik kelapa sawit (Elaeis guineensis Jacq.) pada sistem perendaman sesaat Growth and differentiation of embryogenic callus and somatic embryos of oil palm (Elaeis guineensis Jacq.) in a temporary immersion system - . SUMARYONO; Imron RIYADI; Pauline D. KAS; Gale GINTING (Menara Perkebunan, 2007)
SummaryIn temporary immersion system (TIS),plant materials are exposed to the medium fora short time, therefore they are more exposedto the air and a lack of oxygen frequentlyexperienced by a liquid culture can be avoided.This experiment was conducted to determinethe procedure for callus proliferation up tosomatic embryo germination of oil palm(Elaeis guineensis Jacq.) in TIS culture.Embryogenic calli of oil palm clone MK 638from Marihat Research Institute were culturedon solid medium in the dark culture room andthen used as materials for TIS. Immersion timefor all cultures was three minutes every sixhours. Callus proliferation was conducted inDF liquid culture with 5 mg/L 2,4-D and0.1 mg/L kinetin with transfer interval of 4, 6and 8 weeks. The treatments for somaticembryo maturation were kinetin and ABA,whereas for somatic embryo germination wasIBA, kinetin and GA 3 . The results show thatthe best transfer interval for callus proli-feration was four weeks. In this treatment therelative growth rate of callus was0.38 g/g/week. Somatic embryo initiation fromthe callus was done in DF mediumsupplemented with 1 mg/L 2,4-D and 0.1 mg/Lkinetin. The percentage of somatic embryowas 80% based on biomass fresh weight afterthe fourth subculture. The addition of 0.5 mg/Lkinetin and 0.05 mg/L ABA improved somaticembryo maturation of oil palm; the averagenumber of somatic embryos at advanced stages(torpedo and cotyledonary) was 16.3 embryosper flask. The addition of 2 mg/L IBA and0.5 mg/L kinetin in DF medium with half-strength macro-salt enhanced significantly thegermi-nation of somatic embryos. GA 3 at0.1 mg/L increased the total number ofgerminants.RingkasanPada sistem perendaman sesaat (SPS),bahan tanam hanya terpapar sebentar dalammedium sehingga paparan dengan udara lebihlama dan kekurangan oksigen yang seringterjadi pada kultur cair dapat diatasi. Penelitianini bertujuan menetapkan prosedur untukperbanyakan kalus embriogenik sampai denganperkecambahan embrio somatik kelapa sawit(Elaeis guineensis Jacq.) dalam kultur SPS.Kalus embriogenik kelapa sawit klon MK 638yang diperoleh dari Balai Penelitian Marihatdiperbanyak pada medium padat di ruang gelapyang kemudian digunakan sebagai bahan untukkultur cair SPS. Lama perendaman semuakultur di SPS diatur tiga menit denganfrekuensi setiap enam jam. Perbanyakan kalusdalam medium cair DF dengan 2,4-D 5 mg/Ldan kinetin 0,1 mg/L dilaksanakan denganinterval subkultur 4, 6 dan 8 minggu.Perlakuan pematangan embrio somatik adalahkinetin dan ABA sedangkan perlakuan untukperkecambahan embrio somatik adalah IBA,kinetin dan GA 3 . Hasil penelitian menunjuk-kan bahwa untuk proliferasi kalus embriogenikkelapa sawit, interval subkultur terbaik adalahempat minggu. Pada perlakuan ini laju tumbuhrelatif kalus mencapai 0,38 g/g/minggu.Inisiasi embrio somatik dari kalus dilakukanpada medium DF ditambah 2,4-D 1 mg/L dankinetin 0,1 mg/L. Persentase embrio somatikmencapai 80% dari total bobot basah biomassasetelah subkultur keempat. Penambahan kinetin0,5 mg/L dan ABA 0,05 mg/L meningkatkanpematangan embrio somatik kelapa sawit; rata-rata jumlah embrio somatik fase lanjut (torpedodan kotiledon) adalah 16,3 embrio per bejana.Penambahan IBA 2 mg/L dan kinetin 0,5 mg/Lpada medium DF dengan setengah garammakro meningkatkan perkecambahan embriosomatik secara nyata. GA 3 0,1 mg/L mening-katkan jumlah kecambah yang terbentuk.